TASK-BASED LANGUAGE TEACHING FOR WORKPLACE-ORIENTED SPEAKING IN VOCATIONAL EDUCATION: A QUALITATIVE CASE STUDY - Annisa Novianti Mawaddah (International Journal of Research on English Teaching and Applied Linguistics, 2025)
English instruction in many vocational schools remains dominated by traditional grammar-focused approaches that offer limited opportunities for authentic speaking practice and do not align with students’ practical learning styles. This study aims to explore the implementation of Task-Based Language Teaching (TBLT) in speaking instruction at a vocational high school and to examine students’ and teachers’ experiences, perceived relevance, and challenges in using TBLT to prepare for workplace communication. Using a qualitative case study design, the research was conducted in one vocational high school within the construction and sanitation program. Data were collected through classroom observations, semi-structured interviews with one English teacher and selected students, and document analysis. The data were analyzed using thematic analysis to identify recurring patterns related to the implementation and impact of TBLT. The findings indicate that TBLT offers meaningful opportunities for students to practice speaking through real-world tasks such as job interview simulations, client–worker role-plays, and technical presentations. Students perceived these activities as relevant to their future careers and reported increased confidence and fluency in speaking English. However, affective factors, such as anxiety and linguistic limitations, remained challenges, particularly during the initial stages of implementation. The study concludes that TBLT is a relevant and practical approach for teaching speaking in vocational contexts, as it supports workplace-oriented communication and aligns with vocational students’ learning needs.